LCT Based Integral Transforms and Hausdorff Operators - Jain, Pankaj; Jain, Sandhya; Stepanov, Vladimir Dmitrievich (Eurasian Mathematical Journal, 2020)
In this paper, it is shown that certain Hausdorff operator and its adjoint are connected by linear canonical sine as well as linear canonical cosine transforms. The results have been proved in one as well as in two dimensions.